2010
DOI: 10.1111/j.1468-1293.2010.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of pneumococcal polysaccharide vaccination in HIV-infected adults: a systematic review

Abstract: ObjectiveThe effectiveness of 23-valent pneumococcal polysaccharide vaccine (PPV-23) in preventing pneumococcal disease in HIV-infected people is a subject of debate. We reviewed the clinical evidence for recommending PPV-23 for use in HIV-infected patients. MethodsA systematic search of peer-reviewed publications (EMBASE, the Cochrane Library, and PubMed/ BioMed Central), the Internet and grey literature was conducted. Three hundred and eighteen documents were reviewed. Studies reporting risk estimates for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 46 publications
(115 reference statements)
2
54
0
1
Order By: Relevance
“…31 In 2010, a review of studies on the clinical efficacy of the non-conjugated polysaccharide vaccine in HIV-infected adults did not yield any definitive evidence of a reduction in pneumonia and pneumococcal infection. 32 The loss of the antibodies induced by the nonconjugated polysaccharide vaccine occurs particularly rapidly in the most severely immunocompromised patients or in patients not (Continued on next page) virologically controlled by cART. 33 Conjugated vaccines induce higher immunogenicity and have been tested in HIV-infected patients.…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%
“…31 In 2010, a review of studies on the clinical efficacy of the non-conjugated polysaccharide vaccine in HIV-infected adults did not yield any definitive evidence of a reduction in pneumonia and pneumococcal infection. 32 The loss of the antibodies induced by the nonconjugated polysaccharide vaccine occurs particularly rapidly in the most severely immunocompromised patients or in patients not (Continued on next page) virologically controlled by cART. 33 Conjugated vaccines induce higher immunogenicity and have been tested in HIV-infected patients.…”
Section: Pneumococcal Vaccinationmentioning
confidence: 99%
“…Current smokers use these therapeutic resources less (OR=0.75 with CI 95% 0.71-0.80), but should be encouraged to receive the prevention of vaccines and stop using tobacco 98 (B). The real benefit of using the pneumococcus vaccine in those with acquired immunodeficiency syndrome is no yet known 99 (B), as the only randomized clinical trial demonstrated that there was no increase in antibodies after vaccination, whether polysaccharide or conjugate 100 (A). Likewise, there is debate regarding the use of the vaccine in alcoholics, as there are reported cases of death from streptococcal sepsis after vaccination 101.102 (C).…”
Section: (B)mentioning
confidence: 99%
“…Despite the limitations by the heterogeneity of study design and execution of these observational studies, the authors concluded that currently available evidence is only moderate to support the routine use of PPV23 in HIV-infected patients and newer or more immunogenic vaccines are needed. 8 With respect to immunogenicity of PPV23, the results of published studies are summarized in Table 1, [31][32][33][34][35][36][37][38][39][40][41] which are much more difficult to interpret than the clinical effectiveness studies because of differences in study design, comparators enrolled, CD4 counts and receipt of antiretroviral therapy, especially cART, of the subjects, pneumococcal serotypes assessed, timing of blood sampling, follow-up duration, methods to assess the response (enzyme-linked immunosorbent assay [ELISA] or opsonophagocytic activity [OPA] assay), definitions used for immune response (fold rise of antibody, antibody concentration, or geometric mean concentration or titer). Despite the renumeration of CD4 counts with cART, several studies have shown that most patients failed to maintain durable antibody response for most serotypes following vaccination with PPV23 over the 5-year follow-up period, especially those who had low CD4 counts at vaccination and uncontrolled HIV replication.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, older age, coinfection with hepatitis viruses, co-morbidities, cigarette smoking, and substance abuse are also associated with an increased risk of pneumococcal pneumonia and/or invasive pneumococcal disease (IPD), defined as isolation of S. pneumoniae from a normally sterile site such as blood, cerebrospinal fluid or pleural fluid, while antiretroviral therapy, influenza vaccination and antibiotic prophylaxis are associated with a decreased risk. 8 Without effective antiretroviral therapy, HIV-infected patients may have more than 100 times higher risk for IPD than age-matched populations, with high recurrence rates (8-25%). 9 For example, in San Francisco, the estimated rate of pneumococcal bacteremia in AIDS patients at the beginning of the HIV epidemic was 9.4 cases per 100 person-years, which was much higher than that in the general population before the HIV epidemic (0.075-0.164 cases per 100 person-years).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation